ผลการบูรณาการไอซีทีในการจัดการเรียนรู้ด้วยโครงการ เรื่อง การอนุรักษ์พลังงานและสิ่งแวดล้อมต่อผลสัมฤทธิ์ทางการเรียน และสมรรถนะสำคัญของผู้เรียนชั้นมัธยมศึกษาปีที่ 5 โรงเรียนศึกษาสงเคราะห์เชียงใหม่ ปีการศึกษา 2553 - ไชยนวล ปัณณิกา (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2015)
ผลการวิจัยพบว่า ผู้เรียนที่เรียนโดยการบูรณาการไอซีทีในการจัดการเรียนรู้ด้วยโครงการ เรื่อง การ อนุรักษ์พลังงานและสิ่งแวดล้อม มีผลสัมฤทธิ์ทางการเรียนคิดเป็นค่าเฉลี่ยร้อยละ 83.70 และจากการ วิเคราะห์อนุทินนักเรียนและครูพบว่า ผู้เรียนได้แสดงความสามารถในสมรรถนะสำคัญ 5 ด้าน คือด้านความ สามารถในการสื่อสาร ด้านความสามารถในการใช้เทคโนโลยี ด้านความสามารถในการคิดด้านความสามารถใน การแก้ปัญหา และด้านการใช้ทักษะชีวิต จากผลการวิจัยแสดงให้เห็นว่า ผู้เรียนมีผลสัมฤทธิ์ทางการเรียนสูง ขึ้นและได้พัฒนาความสามารถในสมรรถนะสำคัญ 5 ด้าน จากการทำชิ้นงานผ่านการบูรณาการเทคโนโลยีเว็บ 2.0 ในการจัดการเรียนรู้ด้วยโครงการ The Results of Integrating ICT with Project-based Learning in the Study of Energy Conservation and Environment toward Learners’ Achievement and Learners’ Key Competencies of Mattayom Suksa 5 Studentsat Suksasongkro Chiang Mai School in Academic Year 2010 This study aimed to investigate the learning achievement and learners’ key competencies of the students who studied the energy conservation and environment through integrating ICT with Project-based learning. The target group was 18 Mattayoum Suksa 5 students of Suksasongkro Chiang Mai school in semester 2 of the academic year 2010. The research instruments were 1) a form for evaluating learning achievement 2) a form for evaluating students’ products 3) students’ journals after producing each product and after finishing teacher’s teaching. All the instruments were checked and proved by the experts before being used to gather data. The obtained data were analyzed by percentage and content analysis. The results were revealed that the mean of percentage of the learning achievement of the target group who studied the energy conservation and environment through integrating ICT with Project-based learning was 83.70. The findings from analyzing the students and teacher’s journals were the students show all five-key competencies : communication capacity, thinking capacity, problem–solving capacity, capacity for applying life skills and capacity for technological application. It’s concluded that the students’ learning achievement was higher and the students could develop their five key competencies after producing learning products through integrating web 2.0 with Project-based learning.